Pengembangam Softskill Social Media Marketing Bagi Komunitas Wanita Disabilitas (HWDI Provinsi Jawa Barat) - Putra, Raditya Pratama; Maryani, Anne; Triwardhani, Ike Junita; Rachmawati, Indri (Universitas Nusantara PGRI Kediri, 2022)
This community service has a goal, namely to foster motivation from participants to develop entrepreneurial insight and to have expertise and confidence in the use of social media as a marketing process for business products. The methods for implementing this service are lectures, discussions/questions, answers, practice/simulations, and games. The results of this service are that the participants understand the concept of entrepreneurship much better with the motivation given, participants are able to identify the difference between conventional and digital marketing, and participants know and are able to apply the concept of social media marketing in their business products. The conclusion of this service is that the participants have the enthusiasm and entrepreneurial spirit for women with disabilities, especially in the city of Bandung to continue to work and develop their skills, grow to understand and develop digital marketing communication strategies and grow the ability to pack persuasive messages through ideal communication skills. This is based on the current conditions where there are more and more businesses, so it requires the readiness of entrepreneurs to package messages ideally and quickly. This step can be done by using social media as a marketing tool or what is known as social media marketing.